2015
DOI: 10.1016/j.jmatprotec.2014.11.045
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of electrohydraulic forming of sheet metal parts

Abstract: Please cite this article as: Mamutov, A.V., Golovashchenko, S.F., Mamutov, V.S., Bonnen, Jn.J.F.,Modeling of electrohydraulic forming of sheet metal parts, Journal of Materials Processing Technology (2014), http://dx.Highlights  Numerical model of EHF process is based upon LS-DYNA software  Practical approach to define energy deposition law in plasma channel is developed  Numerical model of EHF process has been validated experimentally  Results on multistage EHF of an automotive panel illustrated EHF c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 10 publications
3
23
0
1
Order By: Relevance
“…These oscillations are likely to be the results of unstable work of the ignitron, a high-voltage, low inductance switch enabling quick discharge of capacitors through the electrode system. Similar effects were observed in experimental waveforms reported by Mamutov et al (2015). However, the amplitude of oscillations reported by Mamutov et al (2015) were visibly smaller which is most likely due to the substantially larger energy of discharge: 12.1 kJ corresponding to 11 kV reported by Mamutov et al (2015) vs. 3.6 kJ corresponding to 6 kV in the present study.…”
Section: Experimental Ehff Formabilitysupporting
confidence: 87%
See 2 more Smart Citations
“…These oscillations are likely to be the results of unstable work of the ignitron, a high-voltage, low inductance switch enabling quick discharge of capacitors through the electrode system. Similar effects were observed in experimental waveforms reported by Mamutov et al (2015). However, the amplitude of oscillations reported by Mamutov et al (2015) were visibly smaller which is most likely due to the substantially larger energy of discharge: 12.1 kJ corresponding to 11 kV reported by Mamutov et al (2015) vs. 3.6 kJ corresponding to 6 kV in the present study.…”
Section: Experimental Ehff Formabilitysupporting
confidence: 87%
“…Similar effects were observed in experimental waveforms reported by Mamutov et al (2015). However, the amplitude of oscillations reported by Mamutov et al (2015) were visibly smaller which is most likely due to the substantially larger energy of discharge: 12.1 kJ corresponding to 11 kV reported by Mamutov et al (2015) vs. 3.6 kJ corresponding to 6 kV in the present study. The pulse generator used in this study was designed primarily for an energy of discharge in the range of 15-20 kJ.…”
Section: Experimental Ehff Formabilitysupporting
confidence: 87%
See 1 more Smart Citation
“…For the simulation efficiency, plasma part was used instead of the electrodes. This treatment is reasonable because many previous studies [21][22][23] have shown that the numerical model with the plasma part can represents the deformation results well instead of electrodes. The most important factor in the fluid parts is the plasma part that has the forming resource.…”
Section: Finite Element Modeling For Fluid Partsmentioning
confidence: 74%
“…This software can simulate interacting of several fluids and deformable solids objects through using the Arbitrary Lagrangian Eulerian (ALE) algorithm which, in combination with Multi-Material technique and Fluid-Structure Interaction (FSI) technique, eliminates the problem of mesh distortion and allows solving the problem of moving liquids and gases inside of a closed complex shape volume [11]. In the context of EHF, a simulation of a discharge channel in liquid for the case of cylindrical symmetry was done in work [12], and for the case of a chamber with coaxial closely placed electrodesin works [13][14][15][16]. In these works, electric power laws were used to provide input in LS-DYNA for energy deposit laws into the discharge channel.…”
Section: Introductionmentioning
confidence: 99%